Application of ultrasound in the evaluation of renal abscess in a dog - Soares da Silva, Alexandre Redson [UNESP]; Ferraz, Luciano Carvalho; Domingues Gomes, Ana Amelia; Mamprim, Maria Jaqueline [UNESP] (Univ Federal Rural Pernambuco, 2011)
Renal abscesses are rare in dogs and, although its pathogenesis is uncertain, may occur in diabetic patients with pyelonephritis, nephrolithiasis, kidney injuries or after abdominal surgery or kidney biopsy. Because of nonspecific clinical signs, laboratory tests associated with ultrasonography are important to confirm the diagnosis and treatment. Generally, kidney abscesses have sonographic aspects with different degrees of echogenicity such as hypo or hyperechoic, homogeneous or heterogeneous, and may or may not have thickened and hyperechoic walls, depending on its chronicity. Our objective was to report the use of ultrasound as a complementary method in the evaluation of disorders of the urinary tract, focusing on a case of renal abscess in a dog.
Keywords: canine; kidney; ultrasound; renomegaly